Evaluating the nexus between financial deepening and economic growth: evidence from Ukraine - Kondrat, Iryna; Kots, Olha (Ocena relacji między pogłębianiem się rynku finansowego i wzrostem gospodarczym: dowody z Ukrainy, 2018)
In this paper systemic problems of Ukrainian banking sector are reviewed and the solutions are offered. The main objective of the study is to examine the relationship between a financial deepening and economic growth in Ukraine by estimating several multiple regression models over the 1993 to 2015 period. A real GDP growth per capita was used as an indicator for the economic growth. The domestic credit to private sector (% of GDP) was used as an index of financial depth. The study concludes that financial deepening causes a slight impact on the economic growth of Ukraine. A low level of impact is an indicator of a limitedness of lending to the real economy. This means that banking sector has not become the real driving force of the economic growth in Ukraine yet. The study suggests a statement that policy makers should design the policies which will encourage lending especially high tech production, small and mid-size business, micro financing to the real economy to promote economic growth and increase employment
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 1, s. 49-64
Keywords: financial deepening; economic growth; banking sector; multiple regression analysis; pogłębianie się rynku finansowego; wzrost gospodarczy; sektor bankowy; analiza regresji wielokrotnej